THE USE OF MODERN INFORMATION TECHNOLOGIES IN THE PROCESS OF TRAINING FUTURE PRESCHOOL EDUCATORS (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the aim of developing methodological foundations for the use of modern information technologies in the process of training future preschool educators. The following tasks are posed in the article, and their solutions are given: to carry out a theoretical analysis of the problem of formation of teachers' readiness for the implementation of modern technologies of preschool education; to identify the current level of readiness of future and current teachers to use modern technologies of preschool education; to develop a model for the formation of teachers' readiness to implement modern technologies of preschool education and pedagogical conditions to improve their professional level; to test the model of educators' readiness to implement modern technologies of preschool education and determine its effectiveness. The article defines the methods, means and forms of training, developed conclusions.